Leptospirosis awareness and health service access in Coastal Demak - Fatati Larasati (Institute Of Computer Science (IOCS), 2026)
Leptospirosis is a zoonotic disease that remains a significant public health problem in Indonesia. Community knowledge about Leptospirosis and their health service access patterns play an important role in prevention and case management. This study aims to describe the level of knowledge about leptospirosis and the health service access chosen when experiencing illness in Bonang, Demak. A descriptive cross-sectional study was conducted among households in Bonang District. From eight villages with the highest leptospirosis incidence, 96 households were selected using cluster probability sampling. In this study, awareness is operationally defined as the level of knowledge about leptospirosis. Data were collected through a structured questionnaire on leptospirosis knowledge and health service access, and analyzed descriptively to present the distribution of knowledge and health service access. Most respondents had moderate level knowledge of leptospirosis, the majority of respondents understood the definition of leptospirosis but lacked knowledge regarding specific causes, symptoms, and the fact that leptospirosis is not transmitted between humans. In terms of health service access, the majority of respondents preferred practicing doctors as their first point of care. Community knowledge of leptospirosis remains insufficient and requires improvement through more intensive health education. Strengthening the primary health care access system is also necessary to ensure timely and effective case management.